2020
DOI: 10.1186/s13059-020-02164-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific usage of transposable element-derived promoters in mouse development

Abstract: Background Transposable elements (TEs) are a significant component of eukaryotic genomes and play essential roles in genome evolution. Mounting evidence indicates that TEs are highly transcribed in early embryo development and contribute to distinct biological functions and tissue morphology. Results We examine the epigenetic dynamics of mouse TEs during the development of five tissues: intestine, liver, lung, stomach, and kidney. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 130 publications
(232 reference statements)
11
49
0
Order By: Relevance
“…A small number of MER52A copies were lowly methylated in normal breast myoepithelial cells, liver, and pancreas tissues, suggesting that some MER52A copies maintain an active epigenetic state and may provide regulatory functions in normal cells. Finally, we found that several TEs overlapping hypoDMRs in GBM encompassed H3K4me3 signal, a mark of active promoters, in the GBM cell line U87, consistent with previous findings of hypomethylated TEs providing cryptic promoters during tumorigenesis 60 and embryonic development 61 (Fig. 7d ).…”
Section: Resultssupporting
confidence: 92%
“…A small number of MER52A copies were lowly methylated in normal breast myoepithelial cells, liver, and pancreas tissues, suggesting that some MER52A copies maintain an active epigenetic state and may provide regulatory functions in normal cells. Finally, we found that several TEs overlapping hypoDMRs in GBM encompassed H3K4me3 signal, a mark of active promoters, in the GBM cell line U87, consistent with previous findings of hypomethylated TEs providing cryptic promoters during tumorigenesis 60 and embryonic development 61 (Fig. 7d ).…”
Section: Resultssupporting
confidence: 92%
“…A wide range of oncogene-encoding TE-driven TcGTs have been documented in recent surveys of cancer databases (Jang et al 2019;Attig et al 2019), but the role of these transcript variants in physiological conditions remains largely undefined. Tissue-specific TcGTs have also been detected in the mouse developing intestine, liver, lung, stomach and kidney (Miao et al 2020). Here, we demonstrate not only the spatially and temporally orchestrated expression of TcGTs in the developing human brain, but also that these TcGTs are largely organ-and cell type-specific.…”
Section: Discussionsupporting
confidence: 52%
“…Yet the more prevalent retrotransposon exaptation is providing cis-regulatory elements that reprogram host gene expression in various developmental and pathological processes ( 1422 ). Originating from ancient, exogenous retroviruses that no longer mobilize, a subset remain largely intact with LTR elements still harboring functional proviral sequences with intrinsic promoter activity, enhancer activity and splicing donor/acceptor sequences ( 16, 2329 ), which substantially expand host gene regulatory landscape and transcript diversity. Due to their unique evolutionary history, retrotransposon mediated gene regulation is often species-specific( 25 ), and its functional importance in vivo remains largely unclear.…”
Section: Main Textmentioning
confidence: 99%